KOMUNIKASI PERUBAHAN PERILAKU MASYARAKAT DALAM PANDEMIK COVID-19 DI PROVINSI KALIMANTAN SELATAN - Sanusi Sanusi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The trend of the number of Covid-19 sufferers is increasing day by day, on the other hand thegovernment with various programs has been very maximal, how can together with the people be free from this pandemic. In South Kalimantan, a province where the percentage of people exposed to Covid-19 is 0.17%, almost 3 times the national average, only 0.09%. The level of compliance and understanding of health protocols that are not understood by the community is because of ineffective handling communication.This study used observational methods and purposive deep interviews with informants to 60Neighborhood Association who distributed cash social assistance to people affected by Covid-19 in South Kalimantan. Other data was collected through a publication conducted by the Covid-19Emergency Alert Task Force for South Kalimantan Province from March 30, 2020 to September1, 2020.The communication program does not run smoothly between policy holders and the community. Part of the coordination between the central and local governments is not going well. The constraint on the number of Indonesian people is very large and quite wide spread, causing different perceptions, some even are antipathy to government policies. The cooperation and involvement of community role models who have many followers is less clear. Awareness of togetherness to maintain mutual health and the spread of the Covid-19 virus has not been evenly distributed, as well as various terms that are not easily understood properly, are difficult to apply. Likewise, the provision of cash social assistance, which was not balanced with education on the importance of maintaining health protocols and various sanctions, actually resulted in a counterproductive situation. Various communication programs have not fully been able to change people's behavior, they need to be evaluated immediately so that they are more effective in handling Covid-19.